SUITABILITY OF THE ELEOS CORNER YOUTUBE CHANNEL AS A LEARNING MEDIA FOR SPEAKING SKILLS ON THE REISEN THEME FOR GRADE XII STUDENTS BASED ON ATP - Dityo, Alfan; Titaley, Audrey (LATERNE, 2026)
The development of digital technology has opened up opportunities for the use of audiovisual media such as YouTube as a source for learning foreign languages in line with the recent Indonesian curriculum “Kurikulum Merdeka”, which emphasises independence and contextual learning. This study aims to analyse the suitability of videos on the YouTube channel eleos corner as a medium for learning German speaking skills on the Reisen theme for grade 12 middlehigh students based on the Learning Objective Flow (ATP) for speaking skills. Using a quatitative descriptive method, nine videos with Reisen theme were analysed using an assessment instrument compiled based on six media selection criteria by Prastowo (2019). The results of the analysis showed a suitability percentage of 77.5%–95%, with seven videos categorised as ‘highly suitable’ and two videos as ‘suitable’. All videos contained A1–A2 vocabulary and linguistic structures relevant to the context of travel and supported the achievement of ATP speaking skills. Thus, the Eleos Corner channel is suitable for use as an alternative learning medium, although it still requires supporting instruments for learning optimisation.